2018
DOI: 10.3390/molecules23081898
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite Profiles, Bioactivity, and HPLC Fingerprint of Different Varieties of Eucommia ulmoides Oliv.: Towards the Utilization of Medicinal and Commercial Chinese Endemic Tree

Abstract: Eucommia ulmoides Oliv. is widely regarded in China as a precious medicinal and commercial endemic tree. Due to cross-breeding or natural variation of E. ulmoides, the metabolite composition may vary significantly, making control of the medical quality difficult. In order to improve the rational development and utilization, the quality of seven varieties of E. ulmoides were evaluated based on metabolite profiles (total phenolic, total flavonoid, gutta-percha, aucubin, geniposidic acid, chlorogenic acid, genipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 30 publications
1
22
0
Order By: Relevance
“…In the present study, our However, we did not identify the antihypertensive components in the aqueous extract of male flower. Recently, many studies demonstrated that four categories extracted from the leaf and bark of EU including lignans, iridoids, flavonoids, and terpenoids have antihypertensive action [7,27,28], and Bessa et al have separated iridoids and flavonoids from the male flowers of EU [12]; therefore, it is likely that iridoids and flavonoids may account for the antihypertensive effect of the male flowers of EU. Of course, further study will be needed to determine the antihypertensive components of the male flowers of EU.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, our However, we did not identify the antihypertensive components in the aqueous extract of male flower. Recently, many studies demonstrated that four categories extracted from the leaf and bark of EU including lignans, iridoids, flavonoids, and terpenoids have antihypertensive action [7,27,28], and Bessa et al have separated iridoids and flavonoids from the male flowers of EU [12]; therefore, it is likely that iridoids and flavonoids may account for the antihypertensive effect of the male flowers of EU. Of course, further study will be needed to determine the antihypertensive components of the male flowers of EU.…”
Section: Discussionmentioning
confidence: 99%
“…Eucommia ulmoides Oliv., also called Du-Zhong, is a traditional medical plant in China, Korea, and Japan [6,7]. Accumulating evidences suggested Eucommia ulmoides Oliv.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chloramphenicol and tetracycline were treated as positive controls. The 1% DMSO solution was a negative control (Özer et al., 2007; Wu et al., 2018).…”
Section: Methodsmentioning
confidence: 99%
“…The extract sample was stored at 4°C. Active constituents of different EUL extract were qualitatively and quantitatively analyzed by HPLC ( Figure S1; Wu et al, 2018).…”
Section: Preparation and Dose Of Eul Extractsmentioning
confidence: 99%